PENGEMBANGAN LAGU ANAK BERBASIS NILAI KARAKTER RELIGIUS BAGI SISWA SEKOLAH DASAR - Engga Dallion. EW; Juhana Sakmal; Petrus Paulus Mbette Suhendro; Rizqa Ekaputri Nurhapsari; Ernes Eka Putri Aritonang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study is intended to develop children's songs based on religious characters for elementary school students. The research method used is Research & Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This study produced two songs entitled